Synergy of National Food Security System - Mitra Musika Lubis; Koko Junaidi; Rizal Aziz; Gustami Harahap; Siti Sabrina Salqaura (Jurnal Penelitian Pendidikan IPA, 2025)
The high population will have an impact on the food crisis and poverty if it is not balanced with food security. The Indonesian government must be able to formulate a national food policy that can improve food security. The food policy includes the availability of food Supplies in good quantity and quality as well as affordable food prices by the community and safe for consumption. The purpose of this study is to examine the synergy of the national food security system. This type of research is qualitative research with the aim of explaining the phenomenon by reviewing existing data. Data sources are obtained through bibliographic data from manuscripts obtained from Google Scholar and analyzed using the Systematic Literature Review (SLR) which is a method that uses previous evidence-based evidence through reviews, evaluations, structured evaluations, classifications and categorizations. Based on the results of the review, the results of this study include: implementing good governance as a challenge and solution to food security; food security stability also affects price and distribution policies; increasing rice production will make a major contribution to rice production. Superior rice varieties will increase food security and reduce poverty; food distribution is still not optimal so that availability in each region and prices in each region vary.